PENGARUH MEDIA PROMOSI GIZI TERHADAP PENINGKATAN PENGETAHUAN, SIKAP DAN PERILAKU GIZI PADA SISWA SEKOLAH DASAR - Kurdanti, Weni; Khasana, Tri Mei; Fatimah, Ana Sidik (PERSATUAN AHLI GIZI INDONESIA, 2019)
School-age children are approved as agents of change, easy, motivated, and competent. The right media will facilitate the delivery of messages, set more goals, save time, and reduce misunderstanding of the recipient of the message. The study aimed to determine the differences in knowledge about nutrition using pop up book media, PGS cards, and leaflets to improve PGS knowledge, attitudes and behavior in elementary school students. Quasi-experimental research design was pre-post test with control group design in 3 groups in 3 different elementary schools. The sample of 123 students who were divided into intervention groups were given counseling from PGS with pop up book media and PGS cards and control groups using leaflet media. Intervention was given 4 times for 8 weeks (counseling every 2 weeks). Data analysis using paired t-test and ANOVA test. The results of the analysis showed that the highest mean in knowledge score (15.00 ± 3.35) and significant was found in the PGS cards group (p = 0.017). No increase in attitude and behavior scores (p>0.05) in all media. Only the average knowledge score showed a significant difference between media (p = 0.001). Thus, it can be concluded that there are differences in students' knowledge about PGS between before and after PGS counseling using nutritional promotion media (pop up book, PGS card, and leaflets) and otherwise with attitudes and behavior.